2011
DOI: 10.1021/ac202039h
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrous-Acid-Induced Chemiluminescence of Fluorescent Carbon Dots for Nitrite Sensing

Abstract: In this work, chemiluminescent (CL) property of the carbon dots in the presence of peroxynitrous acid was studied. Peroxynitrous acid is formed by online mixing of nitrite and acidified hydrogen peroxide. The CL intensity was increased linearly with nitrite concentration in the range from 1.0 × 10(-7) M to 1.0 × 10(-5) M, and the detection limit was 5.3 × 10(-8) M (signal-to-noise ratio of S/N = 3). This method has been successfully applied to the determination of nitrites in pond water, river water, and pure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
262
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(267 citation statements)
references
References 40 publications
(79 reference statements)
3
262
0
2
Order By: Relevance
“…During the thermal treatment, one serves as the carbon source (either the acid or the base part, dependent on their stability), the other part serves as the surface modifier. Other groups mixed the organic molecules used as the carbon source with some polymers together followed by various kinds of thermal treatments [92,100,132,135,136,142,154,158]. Most of the obtained modified or passivated CDs showed good PL activities.…”
Section: Surface Passivationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the thermal treatment, one serves as the carbon source (either the acid or the base part, dependent on their stability), the other part serves as the surface modifier. Other groups mixed the organic molecules used as the carbon source with some polymers together followed by various kinds of thermal treatments [92,100,132,135,136,142,154,158]. Most of the obtained modified or passivated CDs showed good PL activities.…”
Section: Surface Passivationmentioning
confidence: 99%
“…Lin's group found that the CDs, synthesized from glycerine and PEG using a microwave method, could produce strong CL emission in the presence of NaNO 2 and H 2 O 2 [135]. The CL spectrum of the CDs-NaNO 2 -H 2 O 2 system located in the wide range of 400-600 nm and centered at 520 nm.…”
Section: Chemiluminescencementioning
confidence: 99%
“…The process of transforming chemical energy into light emission [44], a phenomenon known as chemiluminescence (CL), has been an attractive topic of intensive research since 1920s [45,46], in view of its fundamental mechanistic significance and the diversity of practical applications [47][48][49][50][51][52][53][54]. CL-based chemosensors show superior sensitivity which is ascribed to the avoidance of the noise caused by light scattering and feature simpler setup with lower background emissions in comparison with photoluminescence-sensing systems [55,56].…”
Section: Chemiluminescencementioning
confidence: 99%
“…Moreover, they can be functionalized and rendered biocompatible. 33,34 Based on the excellent properties, carbon dots can be made viable for sensors 35 such as biosensors for DNA, 36 nitrite, 37 and phosphate, 38 glucose, 39 a-fetoprotein 40 or metal ions. Carbon dots can be synthesised using eco-friendly processes, such as arc discharge, 41 laser ablation [42][43][44][45][46] carbonization of carbohydrates, electrochemical oxidation, and thermally supported synthesis.…”
Section: Introductionmentioning
confidence: 99%